Non‐surgical manual reduction of indirect inguinal hernias in 89 adult stallions. (19th May 2021) - Baranková, K.; de Bont, M. P.; Simon, O.; Meulyzer, M.; Boussauw, B.; Vandenberghe, F.; Wilderjans, H.
Summary: Background: Indirect inguinal hernia (IIH) is the most commonly reported acquired hernia in adult horses. Outcomes following surgical intervention comprising of immediate ventral midline laparotomy (IVML) and simultaneous castration are well known. The outcome following reduction of IIH utilising a noninvasive manual reduction (MR) technique in a large number of horses has not been previously reported. Objectives: To describe a nonsurgical MR technique developed by the authors and to report our long‐term experiences and clinical outcome. Study design: Retrospective study. Methods: Medical records of 89 stallions presenting with IIH and treated with MR were reviewed. Extensive patient data was collected, with cases grouped based on outcome of the MR procedure and whether or not laparotomy was performed. Data on short‐ and long‐term outcome was obtained. Results: Manual reduction was successful in 80 of 89 (90%) horses. Fifty of 89 (56%) horses were treated with MR only and without exploratory laparotomy. In total 29 of 89 (33%) horses underwent IVML and 10 of 89 (11%) delayed ventral midline laparotomy (DVML). Resections were performed in 6 of 89 (8%) horses. Concurrent small intestinal volvulus was diagnosed in 8 of 89 (9%) horses. Horses undergoing DVML following a successful MR had the highest mortality rates during hospitalisation (4/10, 40%). Short‐term survival was 92% (82/89). Ipsilateral reoccurrence of IIH post‐hospital discharge was recorded in 7 of 47 (15%) horses. Overall long‐term survival with a median of 12 years was 72% (34/47). Main limitations: These include the retrospective nature of data collection, lack of standardised pre‐ and post‐MR clinical assessments and a biased Warmblood population. Conclusions: Manual reduction appears to be a feasible nonsurgical technique to reduce IIH in adult Warmblood horses, with favourable survival rates. Individual case assessment is crucial, as delayed laparotomy may increase mortality rates. Suspicion of concurrent small intestinal volvulus or devitalised small intestine always warrants immediate laparotomy following MR.